DEKONSTRUKSI WAYANG DALAM NOVEL DURGA UMAYI - Mashuri Mashuri (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
AbstractThis study is a summary of reading celebration in effort to identify novel Durga Umayi written by YBMangunwijaya, published in 1991. The approach used ‘reading’ of’ deconstruction. Study focuses on the puppet whichis the dominant discourse in the novel that was published in 1991. The goal of the study is finding the events behindthe ‘text’ puppet in the novel. Apparently there are so many demolition on puppet construction are well established,and proved by the number of ‘trace’ the text read back with no single perspective, contradictory figure, blurring the factfiction, as well as the reversal of values and other binary opposition. The blurring and inversion conception of binaryopposition in this novel is formulated as experimental element that causes ‘decentering’ (center spread).Keywords: puppet, deconstruction, novel